Cambridge english for schools : - Aspinall, Patrica (Cambridge University Press, 1998)
This book is the one of Cambridge English for School series which is the new approach to English. The series has 5 levels: Starter, levels 1-4. Every level consists of Student’s book, workbook, workbook cassette, teacher's book, class cassette, test, test cassette and video. Starter test is a book of photocopyable tests which provides thorough testing for all themes through written progress tests and also listening and speaking section. Every theme contains a quiz in order to test knowledge of the content of the course. The book also includes a full answer key plus tapescripts